Effects of mental disorders on employee innovative performance: Evidence from the Indonesian fertilizer industry - Ibrahim Daud; Sulastini; Husnurrofiq; Erni Alfisah (Contemporary Economics, 2020)
The purpose of this study is to investigate the role of mental disorders in employee innovative performance. Decision making and creativity among the employees of Indonesian fertilizer companies was also considered in this study. By implementing a research survey, 200 questionnaires were distributed among the employees of fertilizer companies. Structural Equation Modeling (SEM) was the preferred method for data collection. The study concludes that mental disorders play a crucial role in employee innovative per formance. The employees suffering from mental disorders do not perform worse and cannot contribute to the innovative activities of the company. Mental disorders decrease the employee performance and influence decision making which further affects innovative performance. Mental disorders also influence employee creativity which affects innovative performance. Therefore, mental disorders have an effect on innovative performance of the employees, as influences decision making and employee creativity.
Keywords: D91; D23; 330; Psychological illness; decision making; creativity; innovative performance; fertilizer companies